Case-control study of prostatic cancer in employees of the United Kingdom Atomic Energy Authority. Issue 6916 (27th November 1993) - Rooney, C; Beral, V; Maconochie, N; Fraser, P; Davies, G
Abstract : OBJECTIVE–To investigate the relation between risk of prostatic cancer and occupational exposures, especially to radionuclides, in employees of the United Kingdom Atomic Energy Authority. DESIGN–Case-control study of men with prostatic cancer and matched controls. Information about sociodemographic factors and exposures to radionuclides and other substances was abstracted and classified for each subject from United Kingdom Atomic Energy Authority records without knowledge of who had cancer. SUBJECTS–136 men with prostatic cancer diagnosed between 1946 and 1986 and 404 matched controls, all employees of United Kingdom Atomic Energy Authority. MAIN OUTCOME MEASURES–Documented or possible contamination with specific radionuclides. RESULTS–Risk of prostatic cancer was significantly increased in men who were internally contaminated with or who worked in environments potentially contaminated by tritium, chromium-51, iron-59, cobalt-60, or zinc-65. Internal contamination with at least one of the five radionuclides was detected in 14 men with prostatic cancer (10%) and 12 controls (3%) (relative risk 5.32 (95% confidence interval 1.87 to 17.24). Altogether 28 men with prostatic cancer (21%) and 46 controls (11%) worked in environments potentially contaminated by at least one of the five radionuclides (relative risk 2.36 (1.26 to 4.43)); about two thirds worked at heavy water reactors (19 men with prostatic cancer and 32 controls (relative risk 2.13 (1.00 to 4.52)). Relative risk of prostatic cancer increased with increasing duration of work in places potentially contaminated by these radionuclides and with increasing level of probable contamination. Prostatic cancer was not associated with exposure to plutonium, uranium, cadmium, boron, beryllium, or organic or inorganic chemicals. CONCLUSIONS–Risk of prostatic cancer risk was increased in United Kingdom Atomic Energy Authority workers who were occupationally exposed to tritium, 51Cr, 59Fe, 60Co, or 65Zn. Exposure to these radionuclides was infrequent, and their separate effects could not be evaluated.